Nurse Staffing Levels and Patient-Reported Missed Nursing Care. Issue 4 (October 2015) - Dabney, Beverly Waller; Kalisch, Beatrice J.
<x xml:space="preserve">Abstract</x> A total of 729 inpatients were surveyed using the MISSCARE Survey–Patient. Missed timeliness, patient reports of the time it took for them to receive care from nursing staff, was negatively associated with total nursing staff hours of care per patient-day (r = −0.09, P = .015), registered nurse (RN) hours per patient-day (r = −0.14, P = .0002), and RN skill mix (r = −0.13, P = .0004). RN skill mix was also a predictor of missed timeliness (P = .01).